Hydrogeochemistry of an ancient groundwater system (Sete Fontes, Braga, Northern Portugal). - Antunes, Isabel Margarida Horta Ribeiro (2017)
[Excerpt] Water supply systems and morphology of ancient cities suggest a strongly constrain between urban development and water sources. The availability and location of water resources are mainly associated to a possible transport to the populations. The ancient drinking water supply system from Sete Fontes (Braga, northern Portugal) was built in the middle-eighteen century, overlaying a much older system with probable Roman origin (Martins et al., 2011), and was used as the main supply system of the city until 1913 (Vieira et al., 2016).Although with some uncertainty, the Sete Fontes area is considered by some authors (e.g., Martins et al., 2011; Martins and Ribeiro, 2012) as part of the main source area of water for the Roman city of Bracara Augusta.[...]